Human Geography in Action - Kuby, Michael; Harner, John; Gober, Patricia (Hoboken, NJ John Wiley & Sons, Inc., 2010)
The new fifth edition enhances coverage in the field by enabling economists and political geographers to work online with GIS maps, spreadsheets, simulations, and animated graphs. The book has been updated to use maps of traditional foods and vernacular phrases for soft drinks to illustrate culture regions. Expanded discussions of migration include a look at international immigration. New material is also presented on the local food movement and the breakdown in negotiations for agricultural trade agreements at the Doha trade summit. In addition, economists and political geographers will find key terms throughout the chapters such as creative class, outsourcing, substitution of capital for labor, and transit-oriented development.
Include Illustrations, Maps and Index.
Keywords: Human geography